2018
DOI: 10.3390/catal8040124
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of South African Coal Fly Ash into High-Purity ZSM-5 Zeolite without Additional Source of Silica or Alumina and Its Application as a Methanol-to-Olefins Catalyst

Abstract: Characteristics of ZSM-5 synthesized from H 2 SO 4 -treated coal fly ash and fused coal fly ash extracts are compared in this study. In the synthesis process, fused coal fly ash extract (without an additional silica source) was used in the synthesis of ZSM-5. The effect of the structure-directing agent (tetrapropylammonium bromide, 1,6-hexanediamine or 1-propylamine) on the properties and methanol-to-olefins (MTO) effectiveness of the fly ash-based ZSM-5 was also investigated. A pure ZSM-5 synthesized from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Besides natural minerals, the residue of natural resources containing silicon or aluminum has also attracted a lot of attention. Missengue et al [24] synthesized ZSM-5 zeolites with a very high purity using South African coal fly ash as the sole precursor. Liu et al also reported that zeolite P1 could be synthesized from fluidized bed fly ash [25].…”
Section: Sustainability Of Raw Materials For Zeolite Synthesismentioning
confidence: 99%
“…Besides natural minerals, the residue of natural resources containing silicon or aluminum has also attracted a lot of attention. Missengue et al [24] synthesized ZSM-5 zeolites with a very high purity using South African coal fly ash as the sole precursor. Liu et al also reported that zeolite P1 could be synthesized from fluidized bed fly ash [25].…”
Section: Sustainability Of Raw Materials For Zeolite Synthesismentioning
confidence: 99%
“…Other applications include CFA utilisation for mine back-filling, as well as agricultural remediation of soil and water treatment using modified CFA [17,23]. Another major area of research in CFA valorisation is the production of value-added, porous materials such as zeolites (i.e., zeolitisation) as well as metal extraction/recovery [24][25][26][27][28][29][30][31][32][33][34][35]. As South Africa is largely reliant on coal for energy production [15], CFA research and the development of various CFA valorisation technologies remain major priorities.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the glassy, aluminosilicate phase of CFA contained the majority of the REE content and a process involving size classification, magnetic separation and hydrothermal treatment was proposed as a method of enriching the REE content of CFA [42]. Zeolitisation is a common method utilised in the transformation of the Si and Al content in CFA into a crystalline, porous material with high industrial value [24][25][26][28][29][30][31][32][33][34]. The distributional fate of elements found in CFA during the process of zeolitisation by two different methods (a two-step process and solid fusion-assisted process) was previously reported in literature [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the synthetic zeolite from FA was widely used to treat gaseous pollutants such as sulfur dioxide [18], nitric oxide, nitrogen dioxide, nitrous oxide, and carbon monoxide [19]. At present, there are many reports about the synthesis of ZSM-5 zeolite from FA [20][21][22][23][24]. ZSM-5 has high Si/Al ratio and is hydrophobic, and it has good affinity for organic compounds in wastewater.…”
Section: Introductionmentioning
confidence: 99%